1995
DOI: 10.3109/10715769509147529
|View full text |Cite
|
Sign up to set email alerts
|

N,N'-Bis-Dibenzyl Ethylenediaminediacetic Acid (Dbed): a Site-Specific Hydroxyl Radical Scavenger Acting as an “Oxidative Stress Activatable” Iron ChelatorIn Vitro

Abstract: During oxidative stress, iron traces are supposed to be released from normal storage sites and to catalyse oxidative damage by Fenton-type reactions. This type of damage is difficult to prevent in vivo except by the use of strong iron chelators such as deferoxamine (affinity constant for Fe(III): log K = 30.8). However, strong iron chelating agents are also suspected to mobilize iron from various storage and transport proteins thereby leading to toxic effects. In contrast, N,N'-bis-dibenzyl ethylenediaminediac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…However, classical powerful Fe chelators may not be suitable for long-term treatment of oxidative stress-associated conditions without systemic Fe overload due to chelator-induced deregulation of physiological Fe homeostasis (Galey 2001). Therefore, an “ideal” Fe chelator to be used in oxidative stress-related conditions should not affect Fe homeostasis, but rather “strategically” chelate Fe only in oxidative cellular environment (Galey et al 1995). Recently, boronate-masked prochelators have been introduced and evaluated (Bureš et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, classical powerful Fe chelators may not be suitable for long-term treatment of oxidative stress-associated conditions without systemic Fe overload due to chelator-induced deregulation of physiological Fe homeostasis (Galey 2001). Therefore, an “ideal” Fe chelator to be used in oxidative stress-related conditions should not affect Fe homeostasis, but rather “strategically” chelate Fe only in oxidative cellular environment (Galey et al 1995). Recently, boronate-masked prochelators have been introduced and evaluated (Bureš et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4a) (Hasinoff et al 1994) and decreases anthracycline-induced radical formation (Hershko et al 1993). Galey et al (1995) introduced an iron chelator which is triggered by oxidative stress. In vitro, the prodrug N,N"-bis-dibenzylethylenediaminediacetic acid (DBED), is converted into the active compound N-(Zhydroxybenzy1)-N'-benzylethylenediaminediacetic acid (HBBED) by treatment with H202 ( fig.…”
Section: Development Of Novel Iron Chelatorsmentioning
confidence: 99%
“…Chronic treatment of rats with the neuroleptics chlorpromazine and haloperidol weakens the bloodbrain barrier and facilitates the uptake of Fe3+ into the brain (Ben-Shachar et al & 1994Leenders et al 1994). As iron may play a major role in neuroleptic-induced dopamine D2 receptor supersensitivity (Ben-Shachar et al inhibition (Galey et al 1995) I ) N-r2-hydroxybenzyl)-N'-benzylethylenediaminediacetic acid, generated in situ from N,N'-bis-dibenzylethylenediaminediacetic acid (DBED) and HzOz. (Morel et al 1995) 1985), this can provide a key to the pathophysiology of tardive dyskinesia and related extrapyramidal motor defects caused by antischizophrenic treatment.…”
mentioning
confidence: 99%
“…These agents include some antibiotics, antineoplastic drugs and central nervous system-active therapeutics, especially neuropeptides [99,100]. To overcome this obstacle, various strategies have been developed, which include osmotic opening of the brain endothelial cell tight junctions [120], prodrug preparation [121,122], and utilization of carrier-mediated transporter systems such as antibodies [123][124][125], carbohydrate conjugation [126][127][128][129], viral and nonviral gene delivery vectors [130][131][132], peptide vectors [133,134], liposomes [135][136][137], micelles [138,139], and nanoparticles [100,102,103,[140][141][142]. While these studies have shown promise, most of these methods have been of limited use [133,140].…”
Section: Strategies For Drug Bbb Penetrationmentioning
confidence: 99%
“…For example, a prochelator has been designed for the purpose of easily entering the BBB. The functional groups of the prochelator are then activated by enzymatic or nonenzymatic reactions after they have entered the target organ [121]. Another example is to use simple inorganic silicate that can form very stable complexes with many metals and probably has the ability to enter the BBB [348].…”
Section: ]mentioning
confidence: 99%